Anatomical framework for pre-operative planning of laparoscopic left-sided colorectal surgery: Potential relevance of the distance between the inferior mesenteric artery and inferior mesenteric vein - Billmann, Franck; Saracevic, Melisa; Schmidt, Constantin; Langan, Ewan Andrew (Annals of anatomy, 2021)
The medial-to-lateral approach is favored by most colorectal surgeons for laparoscopic retroperitoneal dissection and mobilisation of the left colon. The peritoneal access window, i.e. the distance between the inferior mesenteric vein (IMV) and inferior mesenteric artery (IMA) must be large enough to perform the procedure safely and successfully. However, studies investigating the IMA-IMV distance and factors affecting this variable, are scarce. Therefore, we examined the IMA-IMV and D3-IMA distances to determine an anatomical framework on planning and adapting surgical therapy.